Labor economics and labor relations - Reynolds, Lloyd George 1910- (Prentice Hall, 1998)
Reflecting changes in the labor field, this classic has been dramatically revised. Greater emphasis has been placed on gender inequality and antidiscrimination policies, international comparisons, and the effects of shifts from mass production to more flexible production methods. The nine chapters on labor economics have been extensively revised and updated. In addition, a new section on internal labor markets, human resource management, and the compensation policies of firms has been added to complement the four chapters on unions and collective bargaining. Throughout this edition, considerable emphasis is placed on current policy issues and how these issues can be illuminated by recent research in labor economics and industrial relations. The writing style is clear, crisp, and nonmathematical.